2007
DOI: 10.1063/1.2793686
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the switching-off mechanism in Ag+ migration based resistively switching model systems

Abstract: Different coplanar Pt∕Ag structures were prepared by photolithography on SiO2 substrates, and Pt∕H2O∕Ag cells were formed by adding de-ionized H2O to the coplanar Pt∕Ag structures. The Pt∕H2O∕Ag cell is utilized here as a model system, due to the feasibility of visual inspection of the switching process. Bipolar switching was achieved for the cell. Scanning electron microscopy (SEM) investigations demonstrated that the growth and dissolution of Ag dendrites are responsible for the resistive switching. The Ag d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
189
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(198 citation statements)
references
References 20 publications
(9 reference statements)
7
189
0
2
Order By: Relevance
“…1h (highlighted by the upper arrow). It should be noted that the geometry of the filament is of fundamental importance in the operation of resistive memories because, during erasing/programming, the dissolution and recreation of the filaments are expected to occur at the thinnest part of the filament 23 . For ECM memories, this has been argued to be near the active electrode interface 23 , contrary to the findings here showing that the thinnest regions of the filaments are near the inert electrode interface instead (for example, Fig.…”
Section: Ex-situ Tem On Memory Devices Fabricated On Sin X Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…1h (highlighted by the upper arrow). It should be noted that the geometry of the filament is of fundamental importance in the operation of resistive memories because, during erasing/programming, the dissolution and recreation of the filaments are expected to occur at the thinnest part of the filament 23 . For ECM memories, this has been argued to be near the active electrode interface 23 , contrary to the findings here showing that the thinnest regions of the filaments are near the inert electrode interface instead (for example, Fig.…”
Section: Ex-situ Tem On Memory Devices Fabricated On Sin X Membranesmentioning
confidence: 99%
“…We found that the filament growth can be critically dependent on the cation mobility in the dielectric film, and report for the first time two different growth modes including a mode in which the conducting filament starts from the active electrode and grows towards the inert electrode, which was unexpected in theories developed for electrochemical metallization (ECM) memories 1,22 . The erasing mechanism was also studied by monitoring reverse growth of the filaments and the dielectric/inert electrode interface was found to be most important regardless of the filament growth directions, which was once again unexpected in previous hypotheses 22,23 . The growth dynamics and filament structures were systematically studied first for devices based on different switching materials in a lateral structure fabricated on ultrathin membranes (~15-nm-thick SiN x ).…”
mentioning
confidence: 99%
“…1,2 The ECM cell consists of an insulator layer sandwiched between two electrodes, in which one is made from an electrochemically active electrode (AE) metal, such as Ag or Cu, and the other is a counter electrode (CE), such as Pt, Ir, W, or Ag. 3,4 Till now, a large number of ECM cells have been reported, employing various insulating materials such as chalcogenides, [5][6][7][8][9][10][11][12][13] oxides, [14][15][16][17][18][19][20][21][22][23][24] amorphous Si (Refs. 25 and 26) and C, [27][28][29][30] and organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that the Cu filament has to be formed once and later on switching takes place at the interface of the Cu dendrite and the Cu electrode. 14,15 Out of 30 measurements on one sample, 63% of the devices could be formed at 10 nA which is many orders of magnitudes lower than the forming currents necessary in other resistively switching materials, e.g., in TiO 2 . The rest of the devices needed higher currents to achieve a stable on state and repetitive switching.…”
mentioning
confidence: 99%